Partner Farmers’ Perceptions of the Presence of the Palm Oil Company PT Tani Prima Makmur in Anggaberi District, Southeast Sulawesi Province - Milawati Saranani; Mursal Junus; I Made Sukratman (International Journal of Economics and Management Sciences, 2026)
The purpose of this study is to determine the perception of Plasma Farmers/Partners on the Existence of PT. Tani Prima Makmur Oil Palm Plantation, Andabia Village, Anggaberi District, Southeast Sulawesi Province. The number of samples in the study was 54 respondents of partner/plasma farmers. There are two types of data in general, namely quantitative data and qualitative data. The data sources used in this study are primary data and secondary data. The data analysis method in this study is qualitative descriptive analysis, with a qualitative analysis model. With a Likert scale, the measured variables are described into variable indicators. Then the indicators are used as a starting point for compiling instrument items that can be in the form of questions or statements. The answers to each instrument item using a Likert scale have positive questions and negative questions. Based on the results of the analysis, it appears that public perception regarding the economic impact of PT Tani Prima Makmur's activities is assessed as a total score of 574, indicating that the existence of oil palm plantations has a positive impact on improving the economy of partner/plasma farmers. The overall social impact has a total score of 416, which means that the presence of oil palm plantations is perceived to have a negative impact on the social community of partner/plasma farmers.